Bone‐to‐Implant Contact Around Immediately Loaded Direct Laser Metal‐Forming Transitional Implants in Human Posterior Maxilla. Issue 6 (1st June 2013) - Shibli, Jamil A.; Mangano, Carlo; Mangano, Francesco; Rodrigues, José A.; Cassoni, Alessandra; Bechara, Karen; Ferreia, Jose Divino B.; Dottore, Alexandre M.; Iezzi, Giovanna; Piattelli, Adriano
Abstract : Objective: Direct laser metal forming (DLMF) is a procedure in which a high‐power laser beam is directed onto a metal powder bed and programmed to fuse particles according to a computer‐aided design file, generating a thin metal layer. This histologic study evaluated the bone‐to‐implant contact (BIC%) around immediately loaded DLMF transitional implants retrieved after 2 months from posterior human maxillae. Methods: Twelve totally edentulous individuals (mean age, 66.14 ± 2.11 years) received DLMF transitional implants divided in twelve immediately loaded (IL) and twelve unloaded (UI) implants. These transitional implants were placed between conventional implants to support the interim complete maxillary denture during the healing period. After 8 weeks, the transitional implants and the surrounding tissue were removed and prepared for histomorphometric analysis. Results: Mature woven preexisting bone lined by newly formed bone in early stages of maturation were found around all retrieved implants. Histometric evaluation indicated that the mean BIC% was 45.20 ± 7.68% and 34.10 ± 7.85% for IL and UI, respectively ( P <0.05). Conclusion: The present data obtained in humans showed that, although both IL and UI presented good BIC%, IL DLMF implants had a higher BIC% in the posterior maxilla.